Widefield OCT angiography and ultra-widefield multimodal imaging of Susac syndrome. Issue 5 (September 2020) - Giuffrè, Chiara; Miserocchi, Elisabetta; Marchese, Alessandro; Cicinelli, Maria Vittoria; Bruschi, Elena; Querques, Giuseppe; Bandello, Francesco M; Modorati, Giulio M
The aim is to present the changes in ultra-widefield and widefield multimodal imaging, including optical coherence tomography angiography of a 33-year-old woman diagnosed with Susac syndrome, over 1 year of follow-up. Fundus examination and multimodal imaging revealed bilateral arterial occlusion of multiple vascular branches with retinal ischemia. Over 1 year follow-up, best-corrected visual acuity improved while retinal ischemia gradually resolved. Widefield optical coherence tomography angiography showed reperfusion of macular large vessels, but not of the small capillaries. Despite anatomical improvement, functional defects of the visual field persisted. In conclusion, widefield and ultra-widefield imaging provided high-resolution details of the central and peripheral damages in Susac syndrome.